Technology of event approach to forming a sense of patriotism - O. V. Berezhnaya; A. L. Kobleva (Вестник Северо-Кавказского федерального университета)
Introduction. The article studies the ways to form and develop a sense of patriotism among growing youth. The need to solve the problems of patriotic education in the training system is not new, however, as modern pedagogical practice shows, it has not yet lost its relevance. The normative documents regulating educational activities focus on the idea of developing life values and forming the personality of a student who knows the cultural and historical achievements and accepts the traditional values of their country. Thus, the necessity and relevance of the pedagogical search for technologies of patriotic education is substantiated.Goal. The article aims to develop a technology project to foster a sense of patriotism in students based on the principles of the event approach.Materials and methods. The study is based on content analysis and generalization of scientific research, methodological literature, pedagogical experience in the field of patriotic education; the method of constructing a project of event-based technology of patriotic education is used.Results and discussion. Psychological and pedagogical research devoted to the definition of the concepts of “patriot”, “patriotic education”, “event-based approach” and “the essence of the event-based approach to the education of students is reviewed and analyzed”. The article draws attention to the fact that school-age children are most susceptible to patriotic education. The effectiveness of the event approach to the formation of patriotic feelings is revealed and theoretically substantiated. A technology project for an event-based approach to foster a sense of patriotism among students has been developed and described in detail.Conclusion. The authors propose to consider the project of the technology of the event approach to the formation of a sense of patriotism presented in the article as a tool for creating conditions for the emotional experience of feeling love for the homeland and a high level of sense of involvement in its history, culture and destiny.